Differentiation of Bone Marrow Mesenchymal Stem Cells into Neural Lineage Cells Induced by bFGF-Chitosan Controlled Release System. (27th March 2019) - Li, Manli; Zhao, Wen; Gao, Yudan; Hao, Peng; Shang, Junkui; Duan, Hongmei; Yang, Zhaoyang; Li, Xiaoguang
Abstract : Bone marrow mesenchymal stem cells undergo differentiation to different lineages with different efficiencies when induced by different factors. We added a bFGF-chitosan controlled release system (bFGF-CCRS) as an inducer into conditioned medium to facilitate the oriented differentiation of BMSCs into neural lineage cells (eventually mature neurons); furthermore, we synchronized BMSCs to the G0/G1 phase via serum starvation to observe the effect of the inducer on the differentiation direction and efficiency. The nonsynchronized group, chitosan alone (not loaded with bFGF) group, soluble bFGF group, and conditioned medium group served as controls, and we observed the dynamic process of differentiation of BMSCs into neural lineage cells at different time points after the beginning of coculture. We analyzed the binding patterns of bFGF and chitosan and assayed the expression differences of key factors (FGFR1, ERK, and c-fos) and molecular switches (BTG2) that regulate the transformation from cell proliferation to differentiation. We also investigated the potential molecular mechanism of BMSC differentiation into neural lineage cells at a high percentage when induced by bFGF-CCRS.